(untitled) - Nishi, Kazuo (Tokyo,New York, 1985)
This book consists of the following many parts: the architecture of Buddhist temples and Shinto Shrines, residential and urban architecture, battle castles and castles towns, entertainment architecture in the Sukiya spirit.
Keywords: Architecture,Architecture; Designs and plans; Japan,Japan